Analyzing the Effect of Financial Constraints on Technological and Management Innovation in SMEs: A Gender Perspective. - Ruiz-Palomo, Daniel; Fernández-Gámez, Manuel Ángel; León-Gómez, Ana María (SAGE, 2022)
The aim of this research is twofold: establishing whether access to bank financing facilitates innovation in SMEs and whether such effect can be explained from a gender perspective. Using a sample of 310 Spanish SMEs, this study first examines the effect of alleviating financial constraints on both technological and management innovation through a structural equation model. Then, the moderating effect of gender is examined. Our results showed that (a) relaxing financial constraints helps SMEs to innovate in both technological and management innovation, (b) the effect of the relaxation of financial constraints is significantly greater in companies managed by women, and (c) the moderating effect of gender occurs from the double perspective of technological innovation and management innovation. Our empirical results suggest that the gender of the CEO plays a vital moderating role among innovation and financial constraints, providing new evidence about women’s contribution to innovation in SMEs, so these results have practical business and institutional implications as they point out the relevance to promote employment policies that favour the gender diversity of employees at all hierarchical levels of the company
Keywords: Empresas - Finanzas; Pequeñas y medianas empresas - Innovaciones tecnológicas; Empresarias; SMEs; Technological innovation; Management innovation; Financial constraints; Gender